A pressure tensor description for the time-resonant Weibel instability. (17th January 2017) - Sarrat, M.; Del Sarto, D.; Ghizzo, A.
Abstract : We discuss a fluid model with inclusion of the complete pressure tensor dynamics for the description of Weibel-type instabilities in a counterstreaming beam configuration. Differently from the case recently studied in Sarrat et al. ( Europhys. Lett., vol. 115, 2016, 45001), where perturbations perpendicular to the beams were considered, here we focus only on modes propagating along the beams. Such a configuration is responsible for the growth of two kinds of instabilities, the two-stream instability and the Weibel instability, which in this geometry becomes 'time resonant', i.e. propagating. This fluid description agrees with the kinetic one and makes it possible e.g. to identify the transition between non-propagating and propagating Weibel modes, already evidenced by Lazar et al. ( J. Plasma Phys., vol. 76 (1), 2010, p. 49) as a 'slope breaking' of the growth rate, in terms of a merger of two non-propagating Weibel modes.